Anionic Lipids Enriched at the ExPortal of Streptococcus pyogenes - Rosch, Jason W. (American Society for Microbiology, 2007)
The ExPortal of Streptococcus pyogenes is a membrane microdomain dedicated to the secretion and folding of proteins. We investigated the lipid composition of the ExPortal by examining the distribution of anionic membrane phospholipids. Staining with 10-N-nonyl-acridine orange revealed a single microdomain enriched with an anionic phospholipid whose staining characteristics and behavior in a cardiolipin-deficient mutant were characteristic of phosphatidylglycerol. Furthermore, the location of the microdomain corresponded to the site of active protein secretion at the ExPortal. These results indicate that the ExPortal is an asymmetric lipid microdomain, whose enriched content of anionic phospholipids may play an important role in ExPortal organization and protein trafficking.